A Work study on Judy Philippines, Inc. - Valenzuela, Martin (College of Engineering, 1991)
Judy Philippine, Inc., a childrens wear garments exporter, has been chosen as the study site in the quest for a relevant and well-rounded education through applications of the theories and knowledge of Methods Engineering, with basic objectives of improving work methods, working conditions, systems and procedures. Gathering all needed facts about the working system of the company, the study group found that there in between the different processes, there are sufficient storages for processed materials and goods, except at the receiving counter, which caught the groups attention and interest to study. The receiving counter serves as the area where issued goods are turned in as finished goods from the subcontractors. However, there is a bottleneck of the goods at the counter as many subcontractors turn in their finished goods at Judy. The group initially thought of an expansion of the area, but with the help of the counterpart team, the group was led to consider first of the present free scheduled deliveries of the subcontractors, that when a sufficient number of subcontractors come at a certain time leads to an overflow of goods at the counter. The group also noticed that the work method of receiving the goods involved a significant amount of time in placing the goods to a temporary storage, by turning around 180 degrees to throw the counted goods and back to the counter for a number of times until all counted goods are move aside to accomodate the next subcontractor, as the storage boxes are positioned at their backs. For the expansion of the area, the company is limited make any changes due to they only lease the structure, and are not allowed to destroy or put up permanent fixtures. The group suggested an Express Lane for those goods less than 2000 pieces, to accomodate small-scale subcontractors by lessening their queueing time. The group also proposes scheduled deliveries for the plant to be able to plan for reception capacity, and forecasts of deliveries. This will lessen the present overtime of the counter workers. For the methods, the boxes are to be transferred beside the workers for cutting time in no turning back and forth easing effort to be used solely for the counting work (not transport work).